Companion to Northwest Coast and Alaska Native art - Patrello, Christopher (Denver Art Museum, 2020)
This full-color publication highlights beautiful objects-both useful and ceremonial-made by the Indigenous artists of the Northwest Coast and Alaska. Since 1925, the Denver Art Museum has collected both historic and contemporary arts from these regions on the criterion of aesthetic quality. This guide, published on the occasion of the reopening of the Denver Art Museum's permanent collection galleries for Northwest Coast and Alaska Native art, includes seldom-told stories about individual artworks, as well as the museum's history of working with living Native artists. From the 1939 Golden Gate International Exposition to recent commissions by Marianne Nicolson and Michael Nicholl Yahgulanaas, the Denver Art Museum has long been committed to collaborating with and incorporating contemporary artists into the collection. Alongside the museum's first-rate collection, contributions from four contemporary Indigenous artists provide context for historical works created by their cultures.